Leadership Approaches and its Impact on Follower Development and Performance - Kabir, Faria; Islam, Nafiza (Asian Business Review, 2013)
Conceptualization and defining the term leadership as theory is still difficult. To reveal the concept of leadership one common practice can be followed that is describing leaders by using established theories and researches. The current discussion explores two aspects. First, it will show how different theories and researches rise ontological challenges to construct the framework of leadership characteristic and its meaning. Second, in terms of methodological implications whether the selected theories are enough for measuring the role and importance of leadership in Sales Management. The study also determines whether the leadership model can increase sales performance for the organization. Thus the conclusion focuses on the growing importance of positive psychology of leadership concept and its implication in Sales Management. JEL Classification Code: E31